Mobile termination and collusion, revisited - Felix Höffler (Max Planck Institute for Research on Collective Goods, 2006)
The standard model by Laffont, Rey and Tirole (1998) treats termination fees as an instrument to increase market power in a one-shot game of horizontal product differentiation. We offer an alternative view in an infinitely repeated Bertrand competition. We focus on symmetrical calling patterns and investigate simple two-part tariffs for two types, as well as general non-linear tariffs for two types and for a continuum of types. In this framework, termination fees make deviations from the collusive outcome less attractive. The optimum deviation strategy is usually to try to attract the high valuation customers since they exhibit the highest profits. Thus, a deviator will have a pool of high users which will have more outgoing than incoming calls, implying net termination payments. A cooperatively chosen termination rate can increase the deviator's cost and thereby always stabilizes collusion.
Keywords: 380; Two way access; mobile telecommunications; non-linear tariffs